Digital Literacy and Online Marketing Empowerment for PKK Women in Teluk Kecapi - M Arief Rahman; Marti Utari; Fitrianto Puja Kesuma; Nurul Ilma Hasana Kunio; Ferizka Tiara Devani; Lailatur Rahmi; Ade Sukma Wati (Sultan Publsiher, 2026)
This community service article presents the baseline mapping and evidence-informed implementation design of a six-month empowerment program for women members of the Family Welfare Empowerment organization (PKK) in Teluk Kecapi Village, Ogan Ilir, South Sumatra. The partner community manages local food and textile products but faces limited digital confidence, weak brand identity, informal social-media use, and minimal marketplace participation. A participatory approach was designed through needs assessment, socialization, hands-on digital-literacy training, online-marketing practice, branding and packaging improvement, responsible artificial-intelligence education, mentoring, and monitoring. The program uses performance demonstrations, participant portfolios, account-operation checklists, and pre/post instruments. Verified baseline information indicates approximately 60 active PKK members organized in six groups and a product portfolio including crackers, kemplang, banana chips, meatballs, woven fabrics, and jumputan textiles. Because a finalized post-intervention dataset was not available at manuscript preparation, target thresholds are reported transparently as program benchmarks rather than observed effects. The intervention is expected to produce business accounts, improved product identities, promotional content, and a PKK Digital Mobilizer Group. The model offers a practical, measurable pathway for integrating women-led microbusiness development into an inclusive Smart Village agenda.